AC impedance spectroscopy: a new equivalent circuit for titania thick film humidity sensors - Faia, P. M. (2005)
The variation of the electrical signal with humidity in ceramic sensors is originated by the chemical and physical sorptions of water molecules existing in the atmosphere. The aim of the work described in the present paper is to establish an equivalent electrical circuit for the case of two titania thick-film samples. It is shown, at least for the temperature of 23 °C, that the same type of circuit represents adequately these two samples for various relative humidities. Chemisorption and physisorption are responsible for the different charge transport mechanisms - ion hopping, ion diffusion and electrolytic conduction. Complex impedance data were obtained at the temperature of 23 °C and various relative humidities, in the frequency range 0.1 Hz-40 MHz. The best and simpler circuit representation we found, which gives the best fitting for the Cole-Cole and Bode plots, consists of two RC parallel circuits in series with two constant-phase elements (CPEs). The values of the electrical components are tabled and, as an example, the Cole-Cole and Bode plots fitting obtained for one of our samples, the sample B, for 87.5% RH, in the frequency range 0.1 Hz-40 MHz is shown.